First person - Andrea Raposo López-Pastor (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Andrea Raposo López-Pastor is first author on 'Liver-specific insulin receptor isoform A expression enhances hepatic glucose uptake and ameliorates liver steatosis in a mouse model of diet-induced obesity', published in DMM. Andrea is a PhD student in the lab of Manuel Benito at Complutense University of Madrid, Madrid, Spain, investigating mechanisms implicated in progression of fatty liver and its relation with other metabolic pathologies.